The trials of Esarhaddon: the conspiracy of 670 BC - Radner, K. (ISIMU, 2016)
This paper presents an attempt to use the scarce available sources, both textual and archaeological, in order to reconstruct the events leading up to the mass execution of members of the Assyrian governing elite in the year 670 BC.